Ripensare il post-sovietico. Un’introduzione - Marco Puleri (eSamizdat)
In this introduction to the special issue Beyond the Post-: (Post-)Soviet Experience Through (Post-)Colonial Lenses, the author aims to reflect upon the contribution of postcolonial theory to the study of post-Soviet political and cultural dynamics on the occasion of the 30th anniversary of the collapse of the Soviet Union: which postcolonial tools can help us understand and enrich the search for a definition of the post-Soviet as an analytic category? In which ways are the post-Soviet cultures postcolonial? What, on the contrary, makes the geographical area born after the collapse of the Soviet Union different from the so-called ‘Third World’ and its dynamics?